2021
DOI: 10.1128/mbio.02130-21
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone Spy Protects Outer Membrane Proteins from Folding Stress via Dynamic Complex Formation

Abstract: Outer membrane proteins (OMPs) play critical roles in bacterial pathogenicity and provide a new niche for antibiotic development. A comprehensive understanding of the OMP quality control network will strongly impact antimicrobial discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Studies had confirmed that antibacterial drugs were blocked from the target by Omp channels (Omp could restrict the entry of antibacterial drugs into cells by controlling the pore size of the channel) before they entered the bacteria, and it could also form an efflux system to remove the antibacterial drugs that had entered the cell. It was pumped out of the cell, but some antibacterial drugs could achieve an antibacterial effect by increasing the permeability of Omp [ 23 , 24 ]. When a certain Omp function was inhibited, the bacteria would activate the expression of other Omp for their own survival.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had confirmed that antibacterial drugs were blocked from the target by Omp channels (Omp could restrict the entry of antibacterial drugs into cells by controlling the pore size of the channel) before they entered the bacteria, and it could also form an efflux system to remove the antibacterial drugs that had entered the cell. It was pumped out of the cell, but some antibacterial drugs could achieve an antibacterial effect by increasing the permeability of Omp [ 23 , 24 ]. When a certain Omp function was inhibited, the bacteria would activate the expression of other Omp for their own survival.…”
Section: Discussionmentioning
confidence: 99%
“…OMP biogenesis requires a network of chaperones to keep uOMPs in an unfolded but folding-competent state in the aqueous environment of the periplasm. SurA, Skp, DegP, Spy, and FkpA have all been implicated in this periplasmic chaperone network, 8,9 but the function of FkpA with respect to the OMP biogenesis pathway has been less investigated as compared to other chaperones (Figure 7). Here we show that FkpA increases the folded population of OmpA 171 into diC 11 PC LUVs after one hour but decreases the observed rate of OmpA 171 folding.…”
Section: Discussionmentioning
confidence: 99%
“…Major players in the OMP biogenesis chaperone network include SurA, Skp, and FkpA with additional contributions from Spy and the protease chaperone DegP (Figure 1). 8,9 While much of the recent work elucidating the mechanisms of these ATP-independent chaperones focuses on the chaperones SurA and Skp, 10,11,20,21,[12][13][14][15][16][17][18][19] thermodynamic and mechanistic . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major players in the OMP biogenesis chaperone network include SurA, Skp, and FkpA with additional contributions from Spy and the protease chaperone DegP (Figure 1) (He et al, 2021; Missiakas et al, 1996). While much of the recent work elucidating the mechanisms of these ATP‐independent chaperones focuses on the chaperones SurA and Skp (Burmann et al, 2013; Calabrese et al, 2020; Holdbrook et al, 2017; Humes et al, 2019; Jia et al, 2020; Marx et al, 2020a, 2020b; Mas et al, 2020; Pan et al, 2020; Sandlin et al, 2015; Schiffrin et al, 2017; Thoma et al, 2015), thermodynamic and mechanistic information about the function of FkpA in OMP biogenesis remains sparse (Ge et al, 2014; Ruiz‐Perez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%